A review of policy on public sector wage administration and collective bargaining in Nigeria (2000)
"The study examines policy sector wage administration and collective bargaining against the persistent industrial relations crisis that attends public sector wage adjustment in Nigeria. Politicization of wage adjustment in the 1970s by periodic wage commissions has been complicated by the attempt to harmonize wages across the public sector. The Latter virtually choked up collective bargaining machineries in the public sector. This paper calls for the decentralization of wages and collective bargaining in order to free the collective bargaining machineries and the streamlining of supportive institutions for wage administration. Strengthening democracy and the rule of Law in Nigeria will provide room for the crystallization of the rules and regulations that govern wage administration in Nigeria."